Barkhausen noise signal of different steels upon face-turning process - Dawara, V.; Vashista, M.; KhanYusufzai, M.Z. (Springer Verlag, 2019)
This paper deals with understanding the effects of excitation field parameters on the nature of Barkhausen noise profile in order to improve the validity of Barkhausen noise results for the machining process. The experiment has been performed on total of four samples, two of high carbon steel and two of high carbon chromium steel. First, all samples are subjected to process annealing and later one sample of each steel was subjected to face-turning process. Barkhausen noise measurement was performed in two steps: first, magnetizing frequency varied and magnetic field intensity kept constant, and second, magnetic field intensity varied and magnetizing frequency kept constant. Magnetic Barkhausen noise profile is obtained by fitting Gaussian function to the root-mean-square distribution of the Barkhausen signal. The complicated behaviour of the profiles with frequency suggests optimum frequency determined statistically, which reflects the stochastic behaviour and can be applied to describe and control the face-turning process. The peak value of the profiles with amplitude of the sinusoidal magnetic field intensity has found to resemble exponential decay correlation. © 2019, The Brazilian Society of Mechanical Sciences and Engineering.
Keywords: Barkhausen noise signal; Face turning; Magnetic feld intensity; Magnetizing frequency